State Bar Annual Meeting in Monterey-California Women Lawyers Dinner - Watkins, Howard::::::::: (1988)
Mary Louise Frampton, Dale Reid, Judy Soley, Doris Coleman (standing), William Coleman, Carla Jo Dakin, Patience Milrod, Sandra Snyder, and Karen Burt at California Women Lawyers Dinner